Sixth Ezra : the text and origin - Bergren, Theodore A. (Oxford University Press, 1998)
6 Ezra is a short, oracular writing that is included in the biblical Apocrypha as the final two chapters (chapters 15-16) of 4 Ezra or 2 Esdras. Cast as the words of God mediated through an unnamed prophet, the main part of the work sets forth predictions of impending doom for the world. It is reminiscent of, and stands in the tradition of, Jewish and Christian prophetic writings that enunciate God's woes and threats against a sinful humanity, and envisage imminent destruction on the earth as a result. 6 Ezra is also concerned to exhort a group of God's chosen people to remain faithful and resist sin in order to escape the impending destruction. There has never been a major study of 6 Ezra or even a complete critical edition of the book, and indeed little has been written about it since the nineteenth century. This book is designed to fill that gap, offering a detailed analysis of the text itself, and addressing the question of its social setting, provenance, date, religious affiliation, and recensional situation of the text. It will also serve to make this important text accesible to a wider audience, while laying the foundations for its further study.